On the Occasion of the Seventieth Birthday of Professor Chang Kung-Ching (Journal of Partial Differential Equations, 2006)
Professor Kung-Ching Chang (Zhang Gongqing) is an outstanding figure in contemporary Chinese mathematics. He made fundamental contributions to the study of PDEs with discontinuous nonlinearities and that of Harmonic Maps and Minimal Surfaces. He is a leading world expert in studying Infinite-dimensional Morse Theory. Born in the middle of messy wars, and educated at a time when China was going through traumatic modern transformations, Chang overcame unimaginable difficulties to achieve as not only a deep and influential mathematician, but also an admirable human being. He has spent a lifetime on his beloved field of mathematics and has become a source of inspiration for several generations of Chinese mathematicians.